2018
DOI: 10.1590/1809-2950/17000225042018
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à autopercepção de saúde em taxistas

Abstract: RESUMO Objetivou-se neste estudo analisar a associação dos fatores sociodemográficos, ocupacionais, comportamentos de risco e relacionados à saúde com a autopercepção da saúde de taxistas. Trata-se de um estudo transversal realizado com 100 taxistas da cidade de Jequié (BA). Foi utilizado um questionário composto por variáveis sociodemográficas, ocupacionais, comportamentais e de saúde. Para a verificação da associação das variáveis independentes com a percepção de saúde, foi utilizado o teste qui-quadrado de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…We found that ORHDs with debt and more severe family-work conflict are more likely to suffer from psychological stress due to sleep deprivation. These findings are in line with previous works in China, Iran and Brazil, [16][17][18] strengthening the argument that sleep deprivation is a significant risk factor for mental health among ORHDs worldwide.…”
Section: Discussionsupporting
confidence: 92%
“…We found that ORHDs with debt and more severe family-work conflict are more likely to suffer from psychological stress due to sleep deprivation. These findings are in line with previous works in China, Iran and Brazil, [16][17][18] strengthening the argument that sleep deprivation is a significant risk factor for mental health among ORHDs worldwide.…”
Section: Discussionsupporting
confidence: 92%